Variation in behavioral traits of two frugivorous mammals may lead to differential responses to human disturbance. Issue 8 (11th March 2020) - Tédonzong, Luc Roscelin Dongmo; Willie, Jacob; Makengveu, Sandra Tewamba; Lens, Luc; Tagg, Nikki
Abstract: Human activities can lead to a shift in wildlife species' spatial distribution. Understanding the specific effects of human activities on ranging behavior can improve conservation management of wildlife populations in human‐dominated landscapes. This study evaluated the effects of forest use by humans on the spatial distribution of mammal species with different behavioral adaptations, using sympatric western lowland gorilla and central chimpanzee as focal species. We collected data on great ape nest locations, ecological and physical variables (habitat distribution, permanent rivers, and topographic data), and anthropogenic variables (distance to trails, villages, and a permanent research site). Here, we show that anthropogenic variables are important predictors of the distribution of wild animals. In the resource model, the distribution of gorilla nests was predicted by nesting habitat distribution, while chimpanzee nests were predicted first by elevation followed by nesting habitat distribution. In the anthropogenic model, the major predictors of gorilla nesting changed to human features, while the major predictors of chimpanzee nesting remained elevation and the availability of their preferred nesting habitats. Animal behavioral traits (body size, terrestrial/arboreal, level of specialization/generalization, and competitive inferiority/superiority) may influence the response of mammals to human activities. Our results suggest that chimpanzees may survive in human‐encroached areas whenever the availability of their nesting habitat and preferred fruits can support their population, while a certain level of human activities may threaten gorillas. Consequently, the survival of gorillas in human‐dominated landscapes is more at risk than that of chimpanzees. Replicating our research in other sites should permit a systematic evaluation of the influence of human activity on the distribution of mammal populations. As wild animals are increasingly exposed to human disturbance, understanding the resulting consequences of shifting species distributions due to human disturbance on animal population abundance and their long‐term survival will be of growing conservation importance. Abstract : This study explores the influence of human disturbance on the distribution of mammal populations in a human‐dominated landscape and evaluates the behavioral adaptations that condition the response of different animal species to human disturbance, using sympatric gorillas and chimpanzees as focal species. We found that gorillas were more negatively affected by human disturbance than chimpanzees. The differences in behavioral traits, such as dietary specialization/generalization, competitive hierarchy, arboreality/terrestriality, and body size, were associated with different levels of mammal response to human settlements.